2017
DOI: 10.1007/s10549-017-4238-0
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the clinical relevance of biomarkers in early stage breast cancer

Abstract: Patients faced with multi-faceted decisions consider personal experience and perceived risk of recurrent disease. Biomarkers providing information on likelihood of toxicity risk do influence treatment choices, and patients may accept reduced benefit when faced with higher risk of toxicity in the curative setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…Using conjoint analysis techniques may help in identification of trends in general patient preferences over time and detection of relevant shifts in culture. Interestingly, among other recent studies an excellent study by Ballinger et al found patients to tend to favor toxicity concerns over treatment benefit ( 11 , 13 ), while older studies often found survival benefit to be of supreme importance ( 16 , 28 30 ). Clinical trials on population level generally focus on survival benefit as the primary endpoint and most critical aspect of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using conjoint analysis techniques may help in identification of trends in general patient preferences over time and detection of relevant shifts in culture. Interestingly, among other recent studies an excellent study by Ballinger et al found patients to tend to favor toxicity concerns over treatment benefit ( 11 , 13 ), while older studies often found survival benefit to be of supreme importance ( 16 , 28 30 ). Clinical trials on population level generally focus on survival benefit as the primary endpoint and most critical aspect of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The tool of conjoint analysis was implemented to assess different attributes that drive individual patient preferences in regard to taxane-based chemotherapies. Generally, the technique of conjoint analysis is widely used in the medical and non-medical field for assessment of preferences and has been demonstrated to offer a valuable tool to elicit patient preferences or utilities for specific treatments ( 11 14 ). In regard to medical treatment, conjoint analysis has proven to be useful for preference elicitation mainly in cancer therapy ( 11 , 13 , 15 , 16 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] In addition, cross-sectional, retrospective studies have surveyed patients at varying time periods after treatment regarding their recall of symptoms during chemotherapy [9][10][11][12] and the persistence of CIPN after treatment. [6][7][8] In addition, cross-sectional, retrospective studies have surveyed patients at varying time periods after treatment regarding their recall of symptoms during chemotherapy [9][10][11][12] and the persistence of CIPN after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Cancer September 1, 2019 With regard to CIPN in clinical practice, retrospective chart reviews of clinician notes have identified the percentage of patients whose CIPN toxicity warranted dose reduction or treatment discontinuation. [6][7][8] In addition, cross-sectional, retrospective studies have surveyed patients at varying time periods after treatment regarding their recall of symptoms during chemotherapy [9][10][11][12] and the persistence of CIPN after treatment. [13][14][15][16] However, to the best of our knowledge, there are few prospective data regarding possible discrepancies in patient-reported CIPN toxicity experience compared with clinicianassessed CIPN severity gathered continuously throughout active treatment.…”
Section: Introductionmentioning
confidence: 99%